Effects of pCO2 and iron on the elemental composition and cell geometry of the marine diatom Pseudo-nitzschia pseudodelicatissima//(Bacillariophyceae) - Sugie, Koji; Yoshimura, T (Supplement to: Sugie, K; Yoshimura, T (2013): Effects of pCO2 and iron on the elemental composition and cell geometry of the marine diatom Pseudo-nitzschia pseudodelicatissima (Bacillariophyceae). Journal of Phycology, 49(3), 475-488, https://doi.org/10.1111/jpy.12054, 2013)
Partial pressure of CO2 (pCO2) and iron availability in seawater show corresponding changes due to biological and anthropogenic activities. The simultaneous change in these factors precludes an understanding of their independent effects on the ecophysiology of phytoplankton. In addition, there is a lack of data regarding the interactive effects of these factors on phytoplankton cellular stoichiometry, which is a key driving factor for the biogeochemical cycling of oceanic nutrients. Here, we investigated the effects of pCO2 and iron availability on the elemental composition (C, N, P, and Si) of the diatom Pseudo-nitzschia pseudodelicatissima (Hasle) Hasle by dilute batch cultures under 4 pCO2 (~200, ~380, ~600, and ~800 µatm) and five dissolved inorganic iron (Fe'; ~5, ~10, ~20, ~50, and ~100 pmol /L) conditions. Our experimental procedure successfully overcame the problems associated with simultaneous changes in pCO2 and Fe' by independently manipulating carbonate chemistry and iron speciation, which allowed us to evaluate the individual effects of pCO2 and iron availability. We found that the C:N ratio decreased significantly only with an increase in Fe', whereas the C:P ratio increased significantly only with an increase in pCO2. Both Si:C and Si:N ratios decreased with increasing pCO2 and Fe'. Our results indicate that changes in pCO2 and iron availability could influence the biogeochemical cycling of nutrients in future oceans with high- CO2 levels, and, similarly, during the time course of phytoplankton blooms. Moreover, pCO2 and iron availability may also have affected oceanic nutrient biogeochemistry in the past, as these conditions have changed markedly over the Earth's history.
Keywords: Biomass/Abundance/Elemental composition; Bottles or small containers/Aquaria (<20 L); Chromista; Coast and continental shelf; Growth/Morphology; Laboratory experiment; Micro-nutrients; North Pacific; Ochrophyta; Pelagos; Phytoplankton; Pseudo-nitzschia pseudodelicatissima; Single species; Temperate